2010
DOI: 10.1159/000285113
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Psychological Burden of Chronic Kidney Disease among Older Adults

Abstract: Introduction:The purpose of the study is to determine if functional status and quality of life (QoL) vary with glomerular filtration rate (GFR) among older adults. Methods: We studied adults aged 45 years and older participating in the REasons for Geographic And Racial Differences in Stroke ( REGARDS) cohort study. Data included demographic and health information, serum creatinine and hemoglobin, the 4-item Center for Epidemiologic Studies Depression Scale

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 94 publications
4
29
0
3
Order By: Relevance
“…The prevalence of patients with CAD, prevalence of patients with DM, prevalence of patients who smoked, prevalence of patients receiving ESA treatment, patients' BMI, and patients' eGFR did not differ between walking and nonwalking patients. These variables were considered as possible confounders because of their association with exercise, mortality, and RRT (17)(18)(19)(20)(21). Walking was associated with lower overall mortality (SHR, 0.65; 95% CI, 0.51 to 0.81; P,0.001) and RRT risk (SHR, 0.75; 95% CI, 0.69 to 0.80; P,0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of patients with CAD, prevalence of patients with DM, prevalence of patients who smoked, prevalence of patients receiving ESA treatment, patients' BMI, and patients' eGFR did not differ between walking and nonwalking patients. These variables were considered as possible confounders because of their association with exercise, mortality, and RRT (17)(18)(19)(20)(21). Walking was associated with lower overall mortality (SHR, 0.65; 95% CI, 0.51 to 0.81; P,0.001) and RRT risk (SHR, 0.75; 95% CI, 0.69 to 0.80; P,0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Whether or not less severe forms of impaired kidney function (30 ml/min/1.73 m 2 or higher) are associated with more depressive symptoms is still largely unknown. Moreover, the largest study that analyzed the continuous relation between eGFR and depressive symptoms found no significant associations [14]. Moreover, we are aware of only two studies on the association between CKD and depressive symptoms in cohorts of cardiac patients.…”
Section: Introductionmentioning
confidence: 99%
“…In three large cross-sectional studies, including 3700 to ≥ 28,000 patients [1416], those with severe CKD (i.e. with an estimated glomerular filtration rate [eGFR] <30 ml/min/1.73 m 2 ) had more depressive symptoms than those without CKD (eGFR ≥ 60 ml/min/1.73 m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…[6] In this regard, authors [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] have pointed out that patients on chronic HD experience a multitude of symptoms, both physical and psychological, owing primarily to the trajectory of the kidney disease, to the different treatments received, and to their side effects. In a review of the recent literature on the topic, Almutary et al [8] mentioned that the mean number of symptoms per HD patient ranged from 6 to 20 across studies and that the main symptoms reported by CKD patients, including those on HD, were fatigue or lack of energy (81%), feeling drowsy (75%), pain (65%), pruritus (61%) and dry skin (57%).…”
Section: Introductionmentioning
confidence: 99%